Visiting the Remains of the Pakuan Pajajaran Palace: Exploring Cultural Values in the Batu Tulis Area of Bogor - Syarifuddin Latif, Bagus; Ari Wibowo, Toni; Pradini, Gagih; Aditya Pratama, Reza (Jurnal Toursci, 2024)
The Batu Tulis area in Bogor is a historical site that contains traces of the Pakuan Pajajaran Palace, a large kingdom that once existed among the Sunda Tatars. This research aims to uncover the cultural values ​​that still remain in the area through "blusukan" activities, namely direct exploration in the field. The research method used is a qualitative approach with participant observation techniques, in-depth interviews, and literature study. Observations were carried out at various historical sites in Batu Tulis, including the Batu Tulis Inscription, the Runjungpati Site, and a number of building ruins which are believed to be part of the Pakuan Pajajaran Palace. The research results show that the remains of the Pakuan Pajajaran Palace in Batu Tulis not only have high historical value, but also hold various important cultural values. These values ​​include the heritage of traditional Sundanese architecture, mythology, and folklore related to the Pakuan Pajajaran Palace, as well as the local community's religious and spiritual practices. Apart from that, the Batu Tulis area is also a symbol of identity and pride for the people of Bogor, who continue to strive to preserve and introduce this cultural heritage to the younger generation and tourists. Blusukan, as an exploration method, has proven to be effective in digging up in-depth and authentic information about historical sites. Direct interaction with site caretakers, community leaders, and visitors provides richer insight into the cultural and historical meaning contained within. This research also found great potential for developing cultural tourism in Batu Tulis, which can increase awareness and appreciation of the cultural heritage of the Pakuan Pajajaran Palace. This research recommends the need for collaborative efforts between the government, local communities, and academics to develop educational and sustainable cultural tourism programs. Also, improving facilities and infrastructure in the Batu Tulis area is needed to support tourist comfort and safety. In this way, it is hoped that the cultural values ​​of the Pakuan Pajajaran Palace can continue to be preserved and benefit the wider community.